Analisis Manajemen Risiko pada Pekerjaan Bendungan Utama Proyek Bendungan Bulango Ulu - Rizky Dwi Cahyo Harun; Arfan Usman Sumaga; Mohammad Yusuf Tuloli (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Dams are very functional for every region in Indonesia because they can be used for various purposes such as irrigation, power generation and raw water supply. One of the important projects in Gorontalo is the construction of the Bulango Ulu Dam, which functions to regulate water flow, reduce the risk of flooding, provide energy, open up jobs, and encourage economic sectors such as tourism. This study aims to identify the dominant technical risks that occur in the implementation of work in the field and evaluate actions to overcome these risk factors. This research method is by distributing questionnaires to respondents who are the implementing contractors of the Bulango Ulu Dam project. The results of this study are that flooding is the most dominant risk factor that occurs in the implementation of the main dam work on the Bulango Ulu Dam project. As well as actions to overcome this, namely improving flood prediction and early warning by strengthening rain monitoring stations.